Superoxide anion generation response to wound in Arabidopsis hypocotyl cutting - Ren, Xufang; Wang, Mengfang; Wang, Yongshun; Huang, Aixia (Plant signaling & behavior, 2021)
Cutting is a frequently used model to study the process of adventitious root formation, and excision of cuttings leads to rapid wound response signaling. We recently showed that as a wound signal, reactive oxygen species (ROS, mainly hydrogen peroxide) participate in adventitious root induction of hypocotyl cuttings through regulation of auxin biosynthesis and transport. Here, superoxide anion (O 2 −* ), an early type of ROS, exhibited rapid burst at the cutting site immediately in response to wounding in Arabidopsis hypocotyl cuttings. Diphenylene iodonium chloride (DPI, inhibitor of NADPH oxidase) overwhelmingly suppressed O 2 −* propagation through the hypocotyl. Compared to wild type, O 2 −* burst only occur in cut base, and upward transduction were inhibited completely in NADPH oxidase mutant AtRbohD. These results indicate O 2 −* generation and propagation in response to wound and via NADPH oxidase in adventitious root induction of hypocotyl cuttings.